Dampak Celebrity Worship K-Pop terhadap Kesejahteraan Psikologis Remaja Perempuan di Komunitas Engene Medan - Salsabilah Syifa Siregar; Hairani Siregar (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to examine the impact of K-Pop celebrity worship on the psychological well-being of female adolescents in the Engene Medan Community. This quantitative research involved 60 respondents who are members of the community. Data were collected using a questionnaire and analyzed with SPSS 30 through validity and reliability tests, simple linear regression, t-test, F-test, and coefficient of determination (R²). The findings indicate that celebrity worship has a positive and significant effect on psychological well-being. The t-test produced a t-value (4.114) greater than the t-table (2.001) with a significance level of 0.001 < 0.05, while the F-test showed an F-value (16.921) exceeding the F-table (4.01) with the same significance level. The coefficient of determination (R²) of 0.226 shows that celebrity worship accounts for 22.6% of the variance in psychological well-being, while the remaining 77.4% is influenced by other factors not addressed in this study. This research concludes that involvement in celebrity worship activities, particularly at the entertainment-social level, can enhance positive feelings about oneself and improve overall psychological well-being. These findings reinforce the understanding that idolizing celebrities, as long as it remains within reasonable limits, can have a constructive impact on female adolescents.